A non-enteric adenovirus A12 gastroenteritis outbreak in Rio de Janeiro, Brazil - Silvana Augusta Rodrigues Portes; Eduardo de Mello Volotão; Monica Simões Rocha; Maria Cristina Rebelo; Maria da Penha Trindade Pinheiro Xavier; Rosane Maria de Assis; Tatiana Lundgren Rose; Marize Pereira Miagostovich; José Paulo Gagliardi Leite; Filipe Anibal Carvalho-Costa (Memorias do Instituto Oswaldo Cruz, 2016)
A gastroenteritis outbreak that occurred in 2013 in a low-income community in Rio de Janeiro was investigated for the presence of enteric viruses, including species A rotavirus (RVA), norovirus (NoV), astrovirus (HAstV), bocavirus (HBoV), aichivirus (AiV), and adenovirus (HAdV). Five of nine stool samples (83%) from patients were positive for HAdV, and no other enteric viruses were detected. Polymerase chain reaction products were sequenced and subjected to phylogenetic analysis, which revealed four strains and one strain of non-enteric HAdV-A12 and HAdV-F41, respectively. The HAdV-A12 nucleotide sequences shared 100% nucleotide similarity. Viral load was assessed using a TaqMan real-time PCR assay. Stool samples that were positive for HAdV-A12 had high viral loads (mean 1.9 X 107 DNA copies/g stool). All four patients with HAdV-A12 were < 25 months of age and had symptoms of fever and diarrhoea. Evaluation of enteric virus outbreaks allows the characterisation of novel or unique diarrhoea-associated viruses in regions where RVA vaccination is routinely performed.